Entrepreneurial Market Orientation and Marketing Performance: An Evidence From Malang Soybean Cracker Industry - Ananda Sabil Hussein (JURNAL SOSIAL HUMANIORA (JSH), 2019)
This study aims to test the effect of entrepreneurial market orientation (EMO) as the development of entrepreneurial orientation concept. Particularly, this study tested the dimensions of EMO name innovation, customer orientation, market orientation and entrepreneurial orientation on marketing performance. To answer the proposed research objectives, this study used multiple regression analysis. Self-administered questionnaires were distributed into one hundred respondents while only 67 questionnaires collected. The results of multiple regression showed innovation has a positive significant effect on marketing performance. Similar to innovation, this study indicated that customer orientation has a positive significant effect on marketing performance.  As proposed in the hypothesis, this study found that market orientation positively affected marketing orientation. Entrepreneurial orientation as the dimension of EMO was shown to have a significant effect on marketing performance. After the completion of this study, both theoretical and practical contribution are provided.